Conceptual and theoretical approaches to corporate social responsibility, entrepreneurial orientation, and financial performance - Paiva, Inna Sousa; Carvalho, Luísa Cagica 1970- (IGI Global, 2020)
""This book explores new trends in corporate social responsibility, entrepreneurial orientation, and financial performance"--Provided by publisher"--